MEMPROGRAMKAN PENGENALAN BANK SYARIAH DAN LEMBAGA KEUANGAN MIKRO SYARIAH PADA DESA KAREHKEL, KECAMATAN LEUWILIANG, BOGOR. - Rully Trihantana; Alfi Ramadayanti; Ratu Dinny (SAHID DEVELOPMENT JOURNAL, 2022)
This community service activity discusses the introduction of Sharia Banks and ShariaMicrofinance Institutions in Desa Karehkel, Kecamatan Leuwiliang,Kabupaten Bogor. Thepurpose of this community service activity is to provide an introduction to Sharia Banks andSharia Microfinance Institutions to the people of Desa Karehkel, Kecamatan Leuwiliang,Kabupaten Bogor with the hope that the community can better understand the existence of ShariaBanks and Sharia Microfinance Institutions. The community service method used is the method oftransparency, participation, and accountability. Community service is also prospective. The resultof this activity is that it can provide insight to the people of Desa Karehkel, KecamatanLeuwiliang, Kabupaten Bogor about Sharia Banks and Sharia Microfinance Institutions in detail